School Responsiveness and Psychosocial Stability of Teachers, Parents, and Learners on the Implementation of Learning Delivery Modalities (LDMs): A Basis in Policy Brief Formulation - Oribiana, Susan; Palanas, Dexter; Fuego, Ligaya (JPAIR Multidisciplinary Research, 2022)
Pedagogy, technology, and material resources are some challenges in ensuring the continuity of learning, while teachers, parents, and learners are factors that significantly affect the school’s learning performance. The Department of Education mandate schools and learning centers to implement capacity building and establish support mechanism to ensure the seamless transition of learning activities into the New Normal. The objective of the study is to understand how parents, learners, and teachers will be able to adjust to the new learning setup, embrace the changes, and affects the delivery and acquisition of new learning, as well as the implications of the pandemic in the participant’s personality. A sequential explanatory research design was used in the study. Data were collected in two consecutive phases. First phase data were computed from the responses in the survey questionnaire, while the second phase responses from focus group discussion used thematic analysis. Based on the generated themes, a new intervention model, Three-way Teaching and Learning Process in the New Normal, was established. The model integrates significant processes such as observation, communication, instruction, interaction, support, and participation in ensuring the success of the new learning set-up. The model also shows interventions highlighted, such as communication access, professional development, digital collaboration, independent learning, stakeholder engagement, and parental education. The intervention model is recommended to be used as an implementation framework in the Division and School Learning Continuity Plan.
Keywords: Education; distance learning delivery modalities; intervention model; mixed-method design; Philippines